The value of a superior vena cava collapsibility index measured with a miniaturized transoesophageal monoplane continuous echocardiography probe to predict fluid responsiveness compared to stroke volume variations in open major vascular surgery: a prospective cohort study - Bubenek-Turconi, Şerban-Ion (J Clin Monit Comput, 2019)
Superior vena cava collapsibility index (SVC-CI) and stroke volume variation (SVV) have been shown to predict fluid responsiveness. SVC-CI has been validated only with conventional transoesophageal echocardiography (TEE) in the SVC long axis, on the basis of SVC diameter variations, but not in the SVC short axis or by SVC area variations. SVV was not previously tested in vascular surgery patients. Forty consecutive adult patients undergoing open major vascular surgical procedures received 266 intraoperative volume loading tests (VLTs), with 500 ml of gelatine over 10 min. The hSVC-CI was measured using a miniaturized transoesophageal echocardiography probe (hTEE). The SVV and cardiac index (CI) were measured using Vigileo-FloTrac technology. VLTs were considered ‘positive’ (≥ 11% increase in CI) or ‘negative’ (< 11% increase in CI). We compared SVV and hSVC-CI measurements in the SVC short axis to predict fluid responsiveness. Areas under the receiver operating characteristic curves for hSVC-CI and SVV were not significantly different (P = 0.56), and both showed good predictivity at values of 0.92 (P < 0.001) and 0.89 (P < 0.001), respectively. The cutoff values for hSVC-CI and SVV were 37% (sensitivity 90%, specificity of 83%) and 15% (sensitivity 78%, specificity of 100%), respectively. Our study validated the value of the SVC-CI measured as area variations in the SVC short axis to predict fluid responsiveness in anesthetized patients. An hTEE probe was used to monitor and measure the hSVC-CI but conventional TEE may also offer this new dynamic parameter. In our cohort of significant preoperative hypovolemic patients undergoing major open vascular surgery, hSVC-CI and SVV cutoff values of 37% and 15%, respectively, predicted fluid responsiveness with good accuracy.